2010
DOI: 10.1021/mp100050d
|View full text |Cite
|
Sign up to set email alerts
|

Enabling the Intestinal Absorption of Highly Polar Antiviral Agents: Ion-Pair Facilitated Membrane Permeation of Zanamivir Heptyl Ester and Guanidino Oseltamivir

Abstract: Anti-viral drugs often suffer from poor intestinal permeability, preventing their delivery via the oral route. The goal of this work was to enhance the intestinal absorption of the low-permeability anti-viral agents zanamivr heptyl ester (ZHE) and guanidino oseltamivir (GO) utilizing an ionpairing approach, as a critical step toward making them oral drugs. The counterion 1-hydroxy-2-napthoic acid (HNAP) was utilized to enhance the lipophilicity and permeability of the highly polar drugs. HNAP substantially inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…This counterion, due to its high lipophilicity, relatively strong binding constant, and a history of prior use with drugs such as salmeterol, zanamivir, and oseltamivir makes it an ideal agent to counterbalance the high polarity of several BCS Class III drugs [5,6]. Miller et al utilized HNAP as a counterion to prepare ion-paired complexes of the oral drugs with poor intestinal permeability such as zanamivir heptyl ester (ZHE) and guanidine oseltamivir (GO) [6]. The study results showed a significant (up to 3.7 log units) increase in the lipophilicity of the drugs due to ion-pairing.…”
Section: Ion-pairingmentioning
confidence: 99%
See 1 more Smart Citation
“…This counterion, due to its high lipophilicity, relatively strong binding constant, and a history of prior use with drugs such as salmeterol, zanamivir, and oseltamivir makes it an ideal agent to counterbalance the high polarity of several BCS Class III drugs [5,6]. Miller et al utilized HNAP as a counterion to prepare ion-paired complexes of the oral drugs with poor intestinal permeability such as zanamivir heptyl ester (ZHE) and guanidine oseltamivir (GO) [6]. The study results showed a significant (up to 3.7 log units) increase in the lipophilicity of the drugs due to ion-pairing.…”
Section: Ion-pairingmentioning
confidence: 99%
“…Over the years, our laboratories have worked with BCS Class III and similar molecules to address permeability issues; mainly by prodrug and permeation enhancer based approaches. Besides that, researchers have explored several other approaches with an aim to tackle the issue of low drug permeability without compromising critical solubility [3,4,5,6,7]. Among the more commonly studied approaches include prodrugs, permeation enhancers, ion-pairing, and other nanotechnology-based approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental octanol-buffer partition coefficients, Log D, for pseudoephedrine and metoprolol at pH 6.5, 7.0, and 7.5 were determined using the traditional shake-flask method (18,19). Briefly, solutions of pseudoephedrine or metoprolol were prepared in octanol-saturated phosphate buffers with pH values of 6.5, 7.0, and 7.5.…”
Section: Determination Of Octanol-buffer Partition Coefficientsmentioning
confidence: 99%
“…The distinction must be made between using complexation to increase aqueous solubility, which is quite common, and to increase membrane permeability. A recently reported example designed to utilize ion pairing is the enhanced intestinal membrane permeability of two poorly permeable antivirals, zanamivir heptyl ester and guanidino oseltamivir, by inclusion of 1-hydroxy-2-naphthoic acid as a counter-ion (14). Sodium N-[8-(2-hydroxybenzoyl)amino]caprylate (also referred to as SNAC) is an absorption enhancer in late-stage clinical trials.…”
Section: Mechanisms Of Absorption Enhancementmentioning
confidence: 99%